2009
DOI: 10.21608/mjae.2009.109488
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pulse Drip Irrigation on Yield and Water Use Efficiency of Potato Crop Under Organic Agriculture in Sandy Soils

Abstract: Pulse drip irrigation is a recent concept where small frequent irrigation applications are applied to saturate the soil and meet the plant water requirements. The field experiment was carried out during two summer growing seasons 2007, it executed in Abo-Ghaleb farm, Cairo-Alex. Rood, 60 Km away from Cairo and the soil was sandy. Seed tubers were planted on 2 th of February and harvested on 28 th of May in two seasons, and the well water was used as irrigation source having EC 1.9 ds/m, the soil sample were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…In terms of irrigation water use efficiency, pulse drip increased productivity in the present study by %0.3 kg of fruit per m 3 of water applied in 2019 and by 1.3 kg of fruit per m 3 of water applied in 2020. Efficiency was much higher during the latter year due to more rain (Table 1) Pulsing resulted in similar increases in irrigation water use efficiency in other crops, including 0.3 kg•m À3 in maize (El-Abedin 2006), 0.8 kg•m À3 in orange (Abdelraouf et al 2019), and 1.2 kg•m À3 in potato (Bakeer et al 2009), but less increase than onion, which was 2.0 to 3.2 kg•m À3 higher with pulsing than with continuous irrigation (Madane et al 2018). Each of these studies clearly indicate that pulsed drip irrigation has the potential to increase production while conserving water.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…In terms of irrigation water use efficiency, pulse drip increased productivity in the present study by %0.3 kg of fruit per m 3 of water applied in 2019 and by 1.3 kg of fruit per m 3 of water applied in 2020. Efficiency was much higher during the latter year due to more rain (Table 1) Pulsing resulted in similar increases in irrigation water use efficiency in other crops, including 0.3 kg•m À3 in maize (El-Abedin 2006), 0.8 kg•m À3 in orange (Abdelraouf et al 2019), and 1.2 kg•m À3 in potato (Bakeer et al 2009), but less increase than onion, which was 2.0 to 3.2 kg•m À3 higher with pulsing than with continuous irrigation (Madane et al 2018). Each of these studies clearly indicate that pulsed drip irrigation has the potential to increase production while conserving water.…”
Section: Resultsmentioning
confidence: 89%
“…2E) and increased number of berries per plant in 2020 (data not shown). Others reported similar benefits to using pulse drip and found it increased production by an average of 2520 kg•ha À1 in strawberry (Gendron et al 2018), 335 kg•ha À1 in green bean (El-Mogy et al 2012), 6630 kg•ha À1 in head lettuce (Almeida et al 2015), 197 kg•ha À1 in maize (El-Abedin 2006), 8382 kg•ha À1 in onion (Madane et al 2018), 5688 kg•ha À1 in orange (Abdelraouf et al 2019), 712 kg•ha À1 in potato (Bakeer et al 2009), and 118 kg•ha À1 in soybean (Eid et al 2013). applied for up to 4 h per day, as needed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other crops, pulse irrigation increased IWUE by 0.8 kgÁm -3 in orange (Abdelraouf et al 2019), 1.2 kgÁm -3 in potato (Bakeer et al 2009), and 2.0 to 3.2 kgÁm -3 in onion (Madane et al 2018). Thus, in these crops, pulse irrigation is a means to increase growth and production with less water; however, this did not appear to be the case for northern highbush blueberry.…”
Section: Resultsmentioning
confidence: 97%
“…Pulse drip irrigation is used in a lot of arid and semi-arid regions, largely to reduce water losses and to improve crop yields and water productivity. Applying pulse drip irrigation technique lead to increase in water movement in horizontal direction more than vertical direction thus increasing in water soil volume (Li, et al, 2004;Bakeer, et al, 2009;Skaggs et al,2010;Abdel tawab, 2015). Ismail, et al, (2014) and Abd-elhakim (2019) reported that the advantage of pulse flow, for reducing the deep percolation of water under the crop root zone, while obtaining a wide horizontal spread of wetting.…”
Section: Introductionmentioning
confidence: 99%